Coalbed Methane As a New Source of Energy in Indonesia and Some Developed Countries; A Review - Awaludin Martin; Hamdani Wahab; Mohammad Barbarosa (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2021)
The decrease in conventional energy sources followed by the world's energy demand as well as mounting concern about climate change, the countries are competing to get new sources of environmentally friendly energy with large reserves. The utilization of CBM as a new energy is an option because of its huge reserves, more environmentally friendly than traditional fossil energy (CBM emissions are 0.39 tones/MWh) and energy efficiency equivalent to natural gas. Indonesia has huge CBM reserves (400 TCF) but has not been utilize optimally due to technological problems, government regulations, large investments and others. This issues plus geographical constraints also occurs in countries with huge CBMs resource such as Russia (450 TCF) and China (700 TCF). Meanwhile, USA (500 TCF) and Australia (500 TCF) already have more established rules and technology. It is necessary to conduct a comparative study from each country according to the applicable regulations to accelerate the utilization of CBM.